Come As You Are – Small Groups in an Online Statistics Course for Highly Heterogeneous Students. (September 2022) - Schützler, Lena; Christ, Oliver
Statistics is not the subject most psychology students are feverishly looking forward to. Fears and doubts about its relevance are quite common. This is especially pronounced at our institution, a large distance-teaching university with highly heterogeneous students. We recognized three clusters of students that might need special support: (1) students with fear of statistics, (2) students whose school time was a long time ago, (3) students who already failed the statistics exam. We gave those students the opportunity to participate in small, supervised groups to discuss learning strategies, problems, or fears. Students who did not participate served as a control group. We exploratively evaluated which kind of students were interested, and if the groups affected attitudes towards statistics, general self-efficacy, and exam-related variables. Interest and activity in the groups were low. No unique effect of participation in the groups on attitudes and grades were observable. Students stated that the groups did not help them to deal with the course. If these results prove stable in further studies with an improved design, one might conclude that setting up such small groups is not worth the effort.